2022
DOI: 10.1039/d2nj00184e
|View full text |Cite
|
Sign up to set email alerts
|

Role of urea on the structural, textural, and optical properties of macroemulsion-assisted synthesized holey ZnO nanosheets for photocatalytic applications

Abstract: Using a macroemulsion-assisted solvothermal method, the present study produces holey ZnO nanosheets exhibiting the hexagonal wurtzite crystal structure. In the synthetic process, urea is employed as a hydrolyzing agent. Its...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…We performed a time-dependent photodegradation study in this work by modifying the method reported in our previous study. 14 In a typical process, 8 mg of the synthesized ZnO was mixed with 8 mL of rhodamine B solution (5 ppm). First, the mixture was stirred in the dark for 5 minutes.…”
Section: Photocatalytic Activity Testmentioning
confidence: 99%
See 4 more Smart Citations
“…We performed a time-dependent photodegradation study in this work by modifying the method reported in our previous study. 14 In a typical process, 8 mg of the synthesized ZnO was mixed with 8 mL of rhodamine B solution (5 ppm). First, the mixture was stirred in the dark for 5 minutes.…”
Section: Photocatalytic Activity Testmentioning
confidence: 99%
“…In our previous work, urea is essential in forming nanostructured ZnO and its properties. 14 The urea hydrolysis is vital for the formation of zinc carbonate hydroxide and the subsequent ZnO crystal. 50,51 Therefore, optimizing the amount of urea resulting in the desired morphology of ZnO is important.…”
Section: Optimization Of the Amount Of Ureamentioning
confidence: 99%
See 3 more Smart Citations